The Impact of Corporate Reputation on Financial Leverage and Trade Credit - Mohsen Khotanlou; Mahdi Kazemiolum; Farzad Ziyaei (راهبرد مدیریت مالی, 2025)
This study aims to investigate the relationship between corporate reputation and financing decisions. In line with the research objectives, the Tehran Stock Exchange accepted 174 companies selected in the 1390 to 1401 period. To measure corporate reputation, a combined scoring approach was used with four components of reputation, including price-to-earnings ratio, Tobin's Q, long-term investment ratio, firm age, and top 100 ranking companies of Industrial Management Organization used as an alternative measure of corporate reputation. Multiple regression with generalized least squares estimation method was used as the primary approach and generalized methods of moments as complementary method for estimating models. Findings showed a positive and significant relationship between corporate reputation score and financial leverage. Also, findings show an inverse and significant relationship between corporate reputation and trade credit. In addition, similar findings were observed using ranking the top 100 companies of the Industrial Management Organization. The supplementary test results with generalized methods of the moments approach have also confirmed the strength of the main results.